The Effect of Intestinal Permeability and Endotoxemia on the Prognosis of Acute Pancreatitis (Gut and Liver, 2012)
Background/AimsEarly intestinal mucosal damage plays an important role in severe acute pancreatitis (AP). Previous studies have shown that intestinal permeability (IP), serum endotoxin and cytokines contribute to the early intestinal barrier dysfunction in AP. This study explored the predictive capacity of IP, endotoxemia and cytokines as prognostic indicators in AP patients.Methods : Eighty-seven AP patients were included in the study. The patients were classified into three groups according to the Balthazar computed tomography severity index (CTSI). We compared the biochemical parameters, including IP, serum endotoxin level and cytokine level among the three groups. The associations of IP with serum endotoxin, cytokines, CTSI, and other widely used biochemical parameters and scoring systems were also examined.Results : IP, serum endotoxin, interleukin (IL-6) and tumor necrosis factor (TNF)-α had a positive correlation with the CTSI of AP. Endotoxin, IL-6, TNF-α, CTSI, the Ranson/APACHE II score, the duration of hospital stay, complications and death significantly affect IP in the AP patients.Conclusion : sWe believe that IP with subsidiary measurements of serum endotoxin, IL-6 and TNF-α may be reliable markers for predicting the prognosis of AP. Further studies that can restore and preserve gut barrier function in AP patients are warranted.